Enhancing glioma treatment with 3D scaffolds laden with upconversion nanoparticles and temozolomide in orthotopic mouse model - Mishchenko, Tatiana A.; Klimenko, Maria O.; Guryev, Evgenii L.; Savelyev, Alexander G.; Krysko, Dmitri V.; Gudkov, Sergey V.; Khaydukov, Evgeny V.; Zvyagin, Andrei V.; Vedunova, Maria V. (Frontiers in Chemistry, 2024)
Targeted drug delivery for primary brain tumors, particularly gliomas, is currently a promising approach to reduce patient relapse rates. The use of substitutable scaffolds, which enable the sustained release of clinically relevant doses of anticancer medications, offers the potential to decrease the toxic burden on the patient’s organism while also enhancing their quality of life and overall survival. Upconversion nanoparticles (UCNPs) are being actively explored as promising agents for detection and monitoring of tumor growth, and as therapeutic agents that can provide isolated therapeutic effects and enhance standard chemotherapy. Our study is focused on the feasibility of constructing scaffolds using methacrylated hyaluronic acid with additional impregnation of UCNPs and the chemotherapeutic drug temozolomide (TMZ) for glioma treatment. The designed scaffolds have been demonstrated their efficacy as a drug and UCNPs delivery system for gliomas. Using the aggressive orthotopic glioma model in vivo, it was found that the scaffolds possess the capacity to ameliorate neurological disorders in mice. Moreover, upon intracranial co-implantation of the scaffolds and glioma cells, the constructs disintegrate into distinct segments, augmenting the release of UCNPs into the surrounding tissue and concurrently reducing postoperative damage to brain tissue. The use of TMZ in the scaffold composition contributed to restraining glioma development and the reduction of tumor invasiveness. Our findings unveil promising prospects for the application of photopolymerizable biocompatible scaffolds in the realm of neuro-oncology.